2019
DOI: 10.1002/jmv.25442
|View full text |Cite
|
Sign up to set email alerts
|

Switching to tenofovir disoproxil fumarate vs continuing treatment in patients with chronic hepatitis B who maintain long‐term virological response to entecavir therapy: A randomized trial

Abstract: No controlled trial in patients with chronic hepatitis B virus (HBV) infection on long-term entecavir (ETV) treatment, comparing switching to tenofovir disoproxil fumarate (TDF) with continuing the therapy, has been reported. Twenty-seven nucleos(t)ide-naïve patients with chronic HBV who underwent ETV therapy for ≥5 years and maintained virological response were included and randomized into two groups: one group continued ETV, and the other switched to TDF, in a 1:2 ratio. The primary endpoint was changed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 25 publications
4
18
0
Order By: Relevance
“…Similar results were also obtained in a randomized controlled study conducted to compare patients in whom the nucleos(t)ide analog was switched from ETV to TAF and those in whom the ETV monotherapy was continued . Although both studies were randomized controlled studies, the study sample size was small in both: 27 patients in the former study and 48 patients in the latter study . Thus, we compared the changes in the serum HBsAg level after drug switching, as compared with the value recorded immediately before the switching, in 91 patients, and found that the degree of reduction of the serum HBsAg level was significantly greater during the TAF administration period than during the ETV administration period, especially in patients without underlying cirrhosis, genotype B HBV infection and serum HBcrAg levels of less than 3.0 log U/mL, even though there was no significant difference in the overall degree of reduction between the two treatment periods.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Similar results were also obtained in a randomized controlled study conducted to compare patients in whom the nucleos(t)ide analog was switched from ETV to TAF and those in whom the ETV monotherapy was continued . Although both studies were randomized controlled studies, the study sample size was small in both: 27 patients in the former study and 48 patients in the latter study . Thus, we compared the changes in the serum HBsAg level after drug switching, as compared with the value recorded immediately before the switching, in 91 patients, and found that the degree of reduction of the serum HBsAg level was significantly greater during the TAF administration period than during the ETV administration period, especially in patients without underlying cirrhosis, genotype B HBV infection and serum HBcrAg levels of less than 3.0 log U/mL, even though there was no significant difference in the overall degree of reduction between the two treatment periods.…”
Section: Discussionsupporting
confidence: 64%
“…In the present study, the virologic and clinical features of patients who had received ETV monotherapy for at least 48 weeks were prospectively evaluated after switching of the nucleos(t)ide analog from ETV to TAF. Recently, Iida‐Ueno et al reported, on the basis of a randomized controlled study in patients receiving ETV monotherapy, that the degree of reduction of the serum HBsAg levels was similar between patients in whom the nucleos(t)ide analog was switched from ETV to TDF and those in whom the ETV monotherapy was continued. Similar results were also obtained in a randomized controlled study conducted to compare patients in whom the nucleos(t)ide analog was switched from ETV to TAF and those in whom the ETV monotherapy was continued .…”
Section: Discussionmentioning
confidence: 99%
“…Since HBsAg loss in ETV therapy is rare, alternative treatments aimed for HBsAg loss are necessary. As an alternative treatment, there have been few reports examining HBsAg reductions following a switch from ETV to TFV . Switching to TFV was not found to enhance HBsAg reduction in these studies; our study also observed similar results.…”
Section: Discussionsupporting
confidence: 81%
“…The primary aim was to evaluate differences in the decrease in HBsAg signal after the treatment switch, but they were not significant in the overall analysis. A similar result for changes in HBsAg was reported recently in a 48-week randomized trial targeting patients who had been treated with ETV for >5 years (19). However, when analyzed in the TDF-switching group in the present study, a greater decrease in HBsAg signal in HBeAg-positive patients compared with HBeAg-negative patients was observed.…”
Section: Discussionsupporting
confidence: 91%
“…4) was removed from the analysis, there was still a similar tendency (P=0.068). As most patients (85%) were HBeAg-negative in the previous study (19), it is possible that switching to TDF in ETV-treated patients may have had an additional effect on the HBsAg decrease only in HBeAg-positive patients. Consistent with this, in treatment-naïve patients, TDF was reported to result in a greater decrease in HBsAg signal in HBeAg-positive patients compared with HBeAg-negative patients (-0.37 vs. 0.07 log IU/ml) (13).…”
Section: Discussionmentioning
confidence: 84%